ISAK 35 to Improve Accountability and Transparency in Nonprofit Organizations: ISAK 35 untuk Meningkatkan Akuntabilitas dan Transparansi Organisasi Nirlaba - Sabrina Adawiyah; Aqwa Naser Daulay; Muhammad Syahbudi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Non-profit organizations, including mosques, face increasing demands for transparent and accountable financial reporting. Specific Background: In Indonesia, ISAK 35 was introduced to enhance financial governance in religious institutions, replacing PSAK 45. Knowledge Gap: Despite growing adoption, few studies assess the practical impact of ISAK 35 on financial reporting quality across different mosque governance models. Aims: This study aims to analyze the application of ISAK 35 in two major mosques in Medan City—Al-Mashun Grand Mosque and the Medan Grand Mosque—and evaluate its role in improving accountability and transparency. Results: Findings reveal significant disparities: Medan Grand Mosque achieved 95% compliance, supported by structured systems and audits, while Al-Mashun scored 65%, with limited reporting practices. Novelty: The study is unique in comparing ISAK 35 implementation across distinct governance structures and linking technical compliance to Sharia ethical values and strategic governance. Implications: Results underscore the need for regulatory support, digital infrastructure, and ethical training to institutionalize ISAK 35. This study contributes to public sector accounting literature and offers practical pathways for professional, transparent mosque financial management in Indonesia.Highlight : The study assessed the implementation of ISAK 35 in two large mosques in Medan City. The results showed differences in compliance levels that reflected the quality of governance. ISAK 35 plays an important role in improving the accountability and transparency of mosque financial reports. Keywords : ISAK 35, Accountability, Transparency, Financial Reports, Religious Non-Profit Organizations